Dynamic Monitoring of Ongoing Clinical Trials. (2nd October 2022) - Xie, Tai; Zhang, Peng; Shih, Weichung Joe; Tu, Yue; Lan, K. K. Gordon
Abstract: In late 2019, the U.S. FDA updated a new Guidance for Industry on Adaptive Designs for Clinical Trials of Drugs and Biologics. The guideline encourages developing and implementing innovative trial designs for future clinical trials. Group sequential, sample size re-estimation, and adaptive group sequential procedures have been very useful for improving the efficiency of conducting trials for decades. However, they face some challenges in operational aspects which limited their potentials. In this article, we introduce a procedure that addresses these issues. Our proposed procedure has the capability of providing anytime accessibility of the whole up-to-date data history. The procedure is largely built on the proven adaptive group sequential design theories and combined with advanced eClinical technologies in trial management to elevate the trial design and monitoring to a more dynamic level. The construct of a new trial monitoring screen is illustrated with real trial examples. The advantages of anytime accessibility of data and the monitoring a trial with the whole data history and trend are delineated. Data monitoring committees, sponsors and regulatory authorities are important stakeholders in the discussion of how future clinical trials should be monitored with respect to timing and frequency.